SANITARY PARASITOLOGICAL AND ECONOMIC EVALUATION OF METHODS FOR DISINFECTION OF WASTEWATER AND MANURE FROM PIG FARMS - R. T. Safiullin; P. V. Novikov (Российский паразитологический журнал, 2016)
Objective of research: the sanitary-veterinary and economic evaluation of the disinfecting effect of different technologies applied for decontamination of livestock manure and sewage from invasive pathogens of pigs as well as for conversion of these wastes.Materials and methods: The degree of contamination of liquid manure from pig farms with eggs and helminth larvae, cysts and oocysts of parasitic protozoa, was studied on the samples collected once a month at farms of theMoscow region, and once every two months at farms of theRepublic ofMordovia. Sampling, transportation and investigation of samples were carried out by the method of A. Cherepanov (1972). Samples were taken in the morning at 3-5 points using IMOP sampler 1000. At the sampling point, an inventory was created where the date, location, selection point and its sample volume were indicated. To prevent the development of microflora in the samples, a certain amount of preserving agent was added. When sampling solid manure fraction from the surface, middle and lower level, manure mass was selected horizontally at each level from 3-5 points, thoroughly mixed, then the averaged sample (1.0 kg) was placed in a plastic bag. To confirm the viability of helminth eggs detected by coproovoscopic examinations, eggs were transferred with a micropipette into Petri dishes and cultured in an thermostat at a temperature 26˚C in a humid environment, periodically aerating and observing the development of the embryo. Comparative assessment of the effectiveness of the treatment facilities in selected pig farms was performed by comparing the number of invasive elements in1 liter of liquid manure entering and flowing out of the treatment facilities.Results and discussion: at all three selected pig farms, the most intense infections with helminth eggs, cysts and oocysts parasitic protozoa were found in raw sewage, what indicates a lack of effectiveness of anti-parasitic measures at the farm.  JSC "Mordovia bacon" with 54 thousand pig heads a year is the only one of three inspected farms, where liquid manure is separated into fractions, followed by disinfestation of solid fraction on concrete pads with further application of manure as an organic fertilizer. Due to mechanical separation of liquid manure into fractions applied at this farm, the number of parasitic elements of internal parasites of pigs (eggs of Ascaris, trihotsefal, esophagitis, coccidia oocysts and cysts balantidiums) in1 kg solid fraction was 586ind. The efficiency of decontamination of liquid manure from parasitic elements, taking into account this treatment method was 53,6-73,4%. Biothermal decontamination of solid fraction of manure piles is achieved within 3-5 months (100%), depending on the season and used in fields as organic fertilizer.